MODE OF ACTION OF HERBAL BIOACTIVE COMPOUNDS SAPONINS AND POLYPHENOLS AGAINST EIMERIA SPP. INFECTION IN BROILER CHICKENS: A REVIEW - Onisa Inggita Putri; Hendi Setiyatwan; Mansyur; Ujang Hidayat Tanuwiria (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Coccidiosis, caused by Eimeria spp., remains a major parasitic challenge in the global poultry industry, leading to significant economic losses due to impaired performance and high mortality rates in poultry. Although synthetic chemoprophylaxis has long been the standard, escalating drug resistance and market demand for chemical-free residues necessitate the development of sustainable alternative strategies to control these parasites. This review critically evaluates the potential integration of phytogenic bioactive compounds, specifically saponins and polyphenols, as future anticoccidial agents. Saponins are amphiphilic glycosides that selectively bind to cholesterol in the Eimeria spp. cell membrane, inducing cellular lysis and interrupting various stages of the parasite's life cycle. Conversely, polyphenols mediate structural damage to the cell walls of sporozoites, which are the most pathogenic stage of coccidia infection. This study synthesizes data on the synergistic modes of action of these two compounds, where the combination of saponin-based membrane destruction and polyphenol-driven cell wall penetration offers comprehensive intestinal protection. By providing a profound understanding of these molecular mechanisms of action, this review aims to establish a robust scientific foundation for developing environmentally friendly, effective, and applicable herbal-based mitigation strategies for the modern poultry industry.